2004
DOI: 10.1210/jc.2003-031238
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling Reveals Coordinated Up-Regulation of Oxidative Metabolism Genes in Thyroid Oncocytic Tumors

Abstract: Oncocytomas are large cell tumors characterized by an abnormal proliferation of mitochondria. To investigate this phenomenon in thyroid oncocytomas, we determined gene expression profiles of 87 samples using microarrays of 6720 PCR products from cDNA clones. Samples included 29 thyroid oncocytomas and six papillary carcinomas, the remainder representing other thyroid pathologies or mitochondria-rich tumor samples, normal thyroid samples, and two thyroid cell lines. Hierarchical clustering and supervised analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 33 publications
7
58
0
Order By: Relevance
“…This might provide the cell with an increased background ERK activity that could account for the low but increased proliferation (Vandeput et al, 2003). The general downregulation of immediate early genes (fos, fosB, egr-1, egr-2, junB, NGFIB, SRF) confirms some previous data obtained by Northern blotting in our group (Deleu et al, 2000) and in thyroid oncocytomas (Baris et al, 2004). This result is not surprising, considering the low proportion of cells in the cell cycle as well as the necessary biphasic nature of the expression of these genes in the G1 phase of the cycle (Reuse et al, 1990;Pirson et al, 1994Pirson et al, , 1996.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This might provide the cell with an increased background ERK activity that could account for the low but increased proliferation (Vandeput et al, 2003). The general downregulation of immediate early genes (fos, fosB, egr-1, egr-2, junB, NGFIB, SRF) confirms some previous data obtained by Northern blotting in our group (Deleu et al, 2000) and in thyroid oncocytomas (Baris et al, 2004). This result is not surprising, considering the low proportion of cells in the cell cycle as well as the necessary biphasic nature of the expression of these genes in the G1 phase of the cycle (Reuse et al, 1990;Pirson et al, 1994Pirson et al, , 1996.…”
Section: Discussionsupporting
confidence: 88%
“…Hierarchical clustering of the genes groups genes encoding mitochondrial proteins and immediate early genes in the upper and lower parts of the panel, respectively (Figure 1). A clustering of such genes has been previously demonstrated in oncocytomas (Baris et al, 2004) and in papillary thyroid carcinomas (Haugen et al, 2003).…”
Section: Analysis Of Separated Samples (Analysis I)mentioning
confidence: 73%
“…Among these 126 genes, the Mitochondrial Ribosomal Protein Large subunit 49 (MRPL49) and 13 genes coding for subunits of the OXPHOS complexes were represented (Baris et al, 2004). A two-step study on the basis of differential display and macroarray analysis of six oncocytic thyroid adenoma samples showed that 12 of the 30 genes upregulated at least two-fold in the tumours were mtDNA-encoded genes (Jacques et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We choose to investigate the thyroid tumours on the basis of their various mitochondrial content, and, in particular, the thyroid oncocytoma, a mitochondrial-rich thyroid tumour characterised by an oxidative metabolism (Savagner et al, 2003;Baris et al, 2004). In oncocytoma, the large majority of the cells show extensive mitochondrial biogenesis; these tumours thereby constitute an interesting model for the study of the expression and localisation of DAP3, as well as its function in the mitochondrial ribosome.…”
mentioning
confidence: 99%
“…There are indications that other important physiological and pathological processes, such as cell differentiation (Angenieux et al, 2001), immortalization (Kim et al, 2001) or tumorigenesis (Ojala et al, 2002;Haugen et al, 2003;Baris et al, 2004), are also associated with alterations in total mitochondrial gene expression. However, the applied algorithm failed to associate these processes with characteristic alterations in expression of mitochondrial transcripts.…”
Section: Discussionmentioning
confidence: 99%